Three-Dimensional Reconstruction of Rolling Contact Fatigue Characteristics - Zeng, Chengkai; Xu, Gaopeng; Li, Hai; Zhu, Gang; Yang, Yan (International Journal of Optics, 2022)
Focusing on the 3D topographic characteristics of rolling contact fatigue, a reconstruction method of the fatigue surface of roller based on point cloud data was proposed in this research. A 3D laser scanner was used to capture the data of point cloud on the surface of the fatigue roller. The gradient segmentation method was used to achieve segmentation of the fatigue contact surface, and the Kd-Tree algorithm in Statistical Outlier Removal filter was adopted to remove different types of noise. The greedy triangulation and hole repair and reconstruction of the curled point cloud were conducted. The experimental results showed that the segmentation accuracy of the fatigue contact surface was above 97.7%, the curling error rate of point cloud was 0.09%, and the maximum deviation of the reconstructed fatigue roller surface was 0.0199 mm. These methods can be applied to analyze the working conditions of roller specimen and contact fatigue.